Output consensus and collision avoidance of a team of flexible spacecraft for on-orbit autonomous assembly. (April 2016) - Chen, Ti; Wen, Hao; Hu, Haiyan; Jin, Dongping
Abstract: Multiple spacecraft that work in concert to assemble as a cohesive unit will play an important role in future space missions. In addition, the individual spacecraft trends to be more and more flexible. A typical flexible spacecraft usually consists of a relatively rigid craft body with one or more flexible appendages, which can be reasonably simplified as free-floating hub-beam system and formulated in a floating frame. The formulation of the network of hub-beam systems is a team of Lagrangian systems in essence. In this study, a compound controller which combines an output consensus controller and a collision avoidance controller to a team of hub-beam systems is proposed. To achieve the assembly mission and suppress the vibration of flexible spacecraft appendages, the design of the control law is decomposed into four steps. Firstly, the hub-beam systems in the team are numbered according to specific rules. Secondly, the attitudes of the hubs are regulated to the desired values synchronously. Thirdly, the whole team of hub-beam systems is driven to the pre-assembly states. Fourthly, the team of hub-beam systems is assembled. In the second and the third step, the compound controller is used to actuate the team to the target configuration. In the fourth step, only the output consensus controller is needed. Finally, two case studies are given to verify the effectiveness of the proposed autonomous assembly strategy. Highlights: Each hub-beam system is under-actuated. The assembly mission is described in four steps. An output consensus and a collision avoidance controller are proposed.